VARIASI PERTUMBUHAN DAN PEMBUAHAN KLON JATI (TECTONA GRANDIS L.F.) UMUR 11 TAHUN - Baskorowati, Liliana; Adinugraha, Hamdan Adma; Mashudi, Mashudi (Bioeksperimen: Jurnal Penelitian Biologi, 2020)
The development of teak clones (Tectona grandis L.f.) is currently being done by industry and farmers to increase productivity. The use of superior teak clones will determine the success of planting; therefore, the superior clones need to be developed. Knowledge of variations in growth and fruiting in the seed orchard of teak clones is important to determine the reproductive capacity of a plant. Therefore, study on variations in the growth and fruiting of teak clones was undertaken. The study was conducted at 11 years old of teak clones, located in Alas Ketu Wonogiri, Central Java. The teak plants measured were planted with a spacing of 2 x 6 m, using a randomized block design, with 100 clones; 3 ramet per clone and consists of 5 blocks as replications. The clones originated from Gunung Kidul, Madiun, Cepu, Wonogiri, Randublatung, Rembang, Muna, Matakidi, Kendari, Buton, and Thailand. All individual tress in the plots were examine for collecting data. Parameters were measured including height of trees, diameter breast height, flower and fruit production. The results showed that height and diameter growth varied significantly between clones, as well as between replications; while flower and fruit production did not show significant differences between clones and between replications. When the clones grouped in height class and diameter class, it showed that the production of flowers and fruits of teak clones were differs significantly. Moreover, the reproductive success of this teak clone seed orchard was very low at 2.15%, suggested due to very little rainfall during the flowering season which causes many flowers to fall out.